Membangun Jembatan antara Matematika dan Coding: Kajian Sistematis terhadap Kurikulum Terpadu STEM - Hamidah, Hamidah; Kusuma, Jaka Wijaya; Rini, Puput Puspito; Slamet, Tri Setyo (Bhinneka Multidisiplin Journal, 2025)
This article presents a systematic review of the integration of mathematics and coding in the integrated STEM (Science, Technology, Engineering, and Mathematics) curriculum. The background of this research is based on the need to improve students' 21st century skills, especially in problem solving, computational thinking, and creativity. The main objective of this study is to identify basic mathematical concepts relevant to coding, the basic principles of coding in STEM contexts, as well as the role of mathematics in designing and analyzing STEM algorithms. The method used includes a systematic literature search through various databases such as JSTOR, ScienceDirect, and Google Scholar, using relevant keywords such as "mathematics", "coding", "STEM", "integrated curriculum", and "computational thinking". Inclusion and exclusion criteria were used to screen for relevant literature, and qualitative data analysis was conducted to synthesize findings from selected studies. Key findings from this study include the identification of key mathematical concepts underlying coding (logic, algebra, calculus), the basic principles of coding in STEM contexts, and case studies of the implementation of integrated mathematics-coding curriculum at various levels of education. The results of the study show that the integration of mathematics and coding can improve students' skills in problem solving, computational thinking, and creativity. In addition, it was found that the role of teachers and lecturers is very important in the successful implementation of this integrated curriculum, which is supported by the use of technology and learning tools. The conclusion of this study is that the integration of mathematics and coding in the STEM curriculum is an effective approach to prepare students for future challenges, as well as provide practical implications for teachers, lecturers, and education students in designing and implementing relevant and engaging learning